Prevalence of Multidrug-Resistant Escherichia coli in Drinking-Water in and around Ayodhya (U.P.) , India - Shekhar, Chandra; Joshi, Namita; Singh, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Thirty five Escherichia coli isolates were recovered from 122 drinking-water samples collected from different sources comprising hand pumps (64), university campus water supplies (23), municipal water supplies (20) and domestic water purifiers (15) from different areas in Ayodhya and Sultanpur districts of Uttar Pradesh. Escherichia coli was isolated, identified, subjected to antimicrobial susceptibility and determination of Multiple Antibiotic Resistance (MAR) index. All Escherichia coli isolates (100%) exhibited resistance against Tetracycline and Furazolidone followed by 94.29, 82.86, 82.86, 71.43, 68.57, 65.71, 51.43, 42.86, 5.71, 5.71, 5.71 and 2.86% isolates against Chloramphenicol, Ampicillin, Amoxicillin/Clavulanic acid, Kanamycin, Nalidixic acid, Trimethoprim, Sulphadiazine, Polymyxin B, Gentamicin, Norfloxacin, Co-trimoxazole, and Streptomycin, respectively. The MAR index of Escherichia coli was 0.55. The presence of Escherichia coli in drinking-water indicates conclusive evidence of recent faecal pollution.